AN IMPROVED METHOD FOR THE COMPUTERISED ANALYSIS OF GR-200A LiF:Mg, Cu, P TL SIGNALS. Issue 2 (28th March 2018) - Cui, H; Tang, K
Abstract: The profile of the residual signals of LiF:Mg, Cu, P within the region of dosimetric interest was approximated by a cubic curve. The conventional analysis, the GCA developed in CIEMAT and the GCA developed in this laboratory were compared. For GCA developed in this laboratory, the 5 μGy test dose could be well measured even after measurement at 10 mGy and obviously at lower doses. The 20 μGy test dose could be well measured even after measurement at 50 mGy. The residual signals caused by previous irradiations in the case of using only reader anneal can be more effectively eliminated by GCA developed in this laboratory than GCA developed in CIEMAT. The program developed in this laboratory, effectively estimating the contribution of the residual signals caused by previous irradiations, permits work to be done using only reader anneal in a dose range of more than three orders of magnitude.